The Catholic Church's Mission with the Marginalized: An Analysis in the Light of the Teachings of Pope Francis's Evangelii Gaudium. (11th May 2020) - Alva, Reginald
Abstract: The Catholic Church's primary mission is to spread the kingdom of God. In the broader sense, the kingdom of God means the reign of righteousness, justice, and peace. However, widespread social, political, and economic inequity tramples the rights of the weak. The church wields tremendous power and influence in the world. However, at times it has failed miserably to protect the weakest. The various scandals within the church call for thorough introspection and repentance. Church authorities need to alter power structures radically to empower the poor and the marginalized. In this paper, I shall refer to Pope Francis's Apostolic Exhortation Evangelii gaudium to propose concrete steps the church could take to reach out to the marginalized, heal their wounds, and collaborate with them to spread the kingdom of righteousness, justice, and peace in this world. Apart from Evangelii gaudium, I shall also refer to the documents on the social teachings of the Catholic Church and the views of experts in this field.